Landscape features and forest maturity promote the occurrence of macroinvertebrates specialized for seepage springs in urban forests in Washington, DC. Issue 5 (15th March 2022) - Burch, Elizabeth; Culver, David C.; Alonzo, Michael; Malloy, Elizabeth J.
Abstract: The hypotelminorheic is a groundwater‐fed shallow subterranean habitat, occurring a few metres below the surface and emerging at a seepage spring. Little is known about the habitat requirements for the amphipods and isopods that live there, and forest quality and other surface parameters have been largely unexplored. Urban parks, encompassing protected lands from ballfields to forests, are not necessarily secure sites, because of non‐compatible uses and changing park boundaries. Almost all records for this fauna in the study area are in parks. Using data from sampling in parklands of south‐east Washington, DC, exploratory analyses were conducted at two spatial scales – the seeps and pervious land patches surrounded by impervious surfaces (which range from 0.59 to 231 ha). Habitat quality, fragmentation and geological variables were calculated, and exploratory logistic regression models were fitted to predict occupancy. Hypotelminorheic macroinvertebrates were found at 66 of 207 seeps and 15 of 27 patches. Five species were collected, three of which were uncommon. Only patches containing three or more seeps and >7.6 ha were inhabited. Occurrence of one or more species in seeps was associated with distance inside the forest, taller tree canopy, elevation and geological formation. There is a threshold amount of habitat below which a population can no longer exist. Few patches of forest remain that are sufficiently large for habitation, and conservation actions should prioritize forested patches with three or more seeps. In addition, the development of forested corridors to enhance connectivity among populations, education of the public about the value of the hypotelminorheic, and development of field methods to detect habitats is recommended. Urban parklands can be important reservoirs for species of conservation concern.